2022
DOI: 10.5603/fhc.a2022.0025
|View full text |Cite
|
Sign up to set email alerts
|

Wedelolactone ameliorates synovial inflammation and cardiac complications in a murine model of collagen-induced arthritis by inhibiting NF-κB/NLRP3 inflammasome activation

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Histochemica et Cytobiologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Scropolioside B, isolated from a Tibetan medicine, Scrophularia dentada Royle ex Benth., could inhibit NF-κB activity, reduce NLRP3 expression, and suppress the maturation and release of IL-1β, suggesting its therapeutic potential in RA and its associated atherosclerosis [ 139 ]. Cao and colleagues demonstrated that Wedelolactone, derived from Eclipta alba, could ameliorate synovial inflammation, cardiac complications, and fibrosis by inhibiting the activation of the NF-κB/NLRP3 inflammasome pathway [ 140 ].…”
Section: Therapeutic Potential By Targeting the Nlrp3 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Scropolioside B, isolated from a Tibetan medicine, Scrophularia dentada Royle ex Benth., could inhibit NF-κB activity, reduce NLRP3 expression, and suppress the maturation and release of IL-1β, suggesting its therapeutic potential in RA and its associated atherosclerosis [ 139 ]. Cao and colleagues demonstrated that Wedelolactone, derived from Eclipta alba, could ameliorate synovial inflammation, cardiac complications, and fibrosis by inhibiting the activation of the NF-κB/NLRP3 inflammasome pathway [ 140 ].…”
Section: Therapeutic Potential By Targeting the Nlrp3 Inflammasomementioning
confidence: 99%
“…HCQ, one of the csDMARDs, may have maculopapular rash, retinopathy, ototoxicity, myopathy, or cardiotoxicity [ 167 , 168 , 169 , 170 ]. The use of IL-β inhibitors, such as anakinra and canakinumab, may exhibit injection site reactions (ISRs) and increase the risk of infection [ 140 , 141 ]. The most common side effect of IL-18BP is ISRs [ 171 ].…”
Section: Therapeutic Potential By Targeting the Nlrp3 Inflammasomementioning
confidence: 99%
“…As with many other medical conditions, 'autoimmune' disorders seem invariably to be associated with an increase in pro-inflammatory transcription factors, including NF-kB [98] and YY1 [99]. This may be an important commonality as both NF-kB and YY1 can upregulate the mitochondrial melatonergic pathway, which may be crucial in determining the course of activation-deactivation in immune cells [63,64].…”
Section: B-cells Antibodies and Mitochondriamentioning
confidence: 99%
“…Notably, MDD pathophysiology seems highly heterogenous [189], with astrocytes being an important hub in coordinating changes in neuronal activity and interarea patterned neuronal activity in the brain [4,179]. However, MDD samples in any given study show significant heterogeneity in physiological indices, the investigation of which should better define the classification and treatment not only of MDD [98,190], but of the associations of MDD with autoimmune disorders.…”
Section: Autoimmunity and Psychiatric Disordersmentioning
confidence: 99%
“…These include traditional Chinese medicine formulas such as the Jinwujiangu capsule for treating RA [196], Baihu-Guizhi decoction [197], and Qi-Sai-Er-Sang-Dang-Song decoction [198]. Additionally, bioactive compounds extracted from plants, such as the monomer derivative of paeoniflorin [199], wedelolactone derived from Xanthium sibiricum [200], licoriceprocessed DGN products containing Huangruixiang [201], a combination of mangiferin and cinnamic acid [202], punicalagin [203], tectoridin [204], strychnine combined with Atractylodes Macrocephala [205], and pinocembrin from the genus Pinus [206], have also shown activity through this pathway.…”
Section: Regulating the Tlr4/nlrp3/nf-kb/gsdmd Signaling Pathwaymentioning
confidence: 99%